Is The Honeymoon Over? The Tumultuous Love Affair Between the Museum and the Arts of Sound - Džuverović, Lina (Circuit, 2020)
This text considers points of intersection between the arts of sound and visual arts institutions and examines their rapidly changing relationships from the beginning of the twenty-firstcentury to the present day. Combining an autoethnographic approach, drawing on the author’s curatorial work with sound-based practices as the director of the London-based commissioning art agency Electra, and sustained observations of broader issues emerging around sound-led work in the field of contemporary art, the text identifies a number of ways in which “sonic substance” enters visual arts institutions. The author considers how these dynamics have changed over the past twenty years and analyses ruptures that emerge along the way.